Design and Development of a Web-Based Information System for the Management and Maintenance of Primary Operational Equipment (ALOPTAMA) at the North Lampung Geophysical Station - Sifa Mis Ayu; Yulina Yulina (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The management and maintenance of primary equipment (ALOPTAMA) at geophysical stations play a crucial role in ensuring the reliability of earthquake observation data and other geophysical phenomena. However, maintenance recording and reporting processes at the Geophysical Station of North Lampung are still conducted using conventional and separated files, which may lead to data duplication, information inconsistency, and delays in report generation. This study aims to design and develop a web-based information system to support the integrated management and maintenance of ALOPTAMA. The system development adopts the Waterfall method, consisting of requirements analysis, system design, implementation, and testing stages. The system is developed using PHP as the programming language, MySQL as the database management system, and AdminLTE as the user interface framework. The results indicate that the developed system effectively facilitates ALOPTAMA data management, inbound and outbound inventory recording, stock monitoring, and automated, structured maintenance reporting. The implementation of the system improves operational efficiency, reduces recording errors, and accelerates the reporting process. Therefore, the proposed information system serves as a digital solution to support ALOPTAMA maintenance operations within the BMKG environment.